Computed Tomography and Ultrasound of Omental Infarction in Children: Differential Diagnoses of Right Lower Quadrant Pain - Lim, Soyeoun; Hong, Hyun Sook; Kim, Young Tong; Lee, Hae Kyung; Lee, Min Hee (Journal of the Korean Society of Radiology, 2013)
Purpose: Omental infarction in children occurs rarely and is often confused with other diseases that cause right lower quadrant (RLQ) pain. This study evaluates ultrasonography (US) and computed tomography (CT) findings of omental infarction in children with abdominal pain. Materials and Methods: The CT and US findings and clinical presentations of nine children diagnosed with omental infarction between 2005 and 2012 were retrospectively reviewed. Results: Distributions of abdominal pain in the patients included RLQ (n = 6), right upper quadrant (RUQ, n = 1), periumbilical (n = 1), and the epigastric (n = 1) region. All patients underwent abdominal CT, and three underwent abdominal US. On CT scan, a typical triangular, heterogeneous fatty mass was seen between the abdominal wall and ascending colon (n = 6) or hepatic flexure (n = 1). A fatty mass with an enhanced rim that mimicked acute appendagitis was present in two patients. The other two patients had diffuse fat infiltration without mass. On US, a heterogeneously hyperechoic omental mass was seen in the RLQ (n = 2) or RUQ (n = 1). Three patients underwent appendectomy and partial omentectomy, and pathology confirmed omental infarction. Conclusion: Knowledge of the typical imaging features of omental infarction and application for diagnosis are important for its differentiation from other conditions that also present with RLQ pain and can avoid unnecessary surgery. KCI Citation Count: 0